Consumption Over Life Cycle Of Remittances Recipients In Indonesia - Ade Jamal Mirdad; Sutyastie Sumitro Remi; Ferry Hadiyanto; Bagdja Muljarijadi (Finance and Business Management Journal, 2023)
Purpose of this study is to examine and analyze the consumption patterns of remittance recipient households using the Life Cycle Hypothesis (LCH) model. Using data from three periods of the IFLS (IFLS 2000, IFLS 2007 and IFLS 2014) and the decomposition of cohort and age effects on consumption, the results show that consumption behavior is not as described as in the LCH theory. The curve of average consumption-age in this remittance recipient household has a "hump shape" pattern.